BOARD KNOWLEDGE AND SUSTAINABILITY REPORT QUALITY - I Gusti Agung Jaya Utama; I Putu Sudana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to examine the effect of board knowledge on sustainability report quality. The research was conducted on cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using a non-probability sampling method with a purposive sampling technique, resulting in 75 observations. Data were collected through documentation methods and analyzed using multiple linear regression analysis with SPSS software. The findings indicate that the educational level and experience of the board of commissioners have a positive effect on sustainability report quality. These results are consistent with agency theory and resource-based theory, suggesting that board knowledge strengthens the monitoring function in ensuring the quality of corporate disclosures. Higher educational attainment and extensive experience among commissioners enhance their capacity to evaluate and provide recommendations regarding sustainability reporting practices. In contrast, the educational level and experience of the board of directors do not significantly affect the quality of corporate sustainability reports.